Resolusi Kurikulum Pendidikan Agama Islam Dalam Menyikapi Era Society 5.0 - Nurut taufik; Siti nasim jf (Indonesia society of applied science, 2024)
This article discusses the readiness of the next generation of civilization in the era of society 5.0 by looking at the opportunities, challenges, abilities of individuals and other human resources so that in the future they can compete and be able to solve the problems that are in front of them by utilizing the abilities developed in education, and This is to welcome the hustle and bustle of community life in the 5.0 era which is full of challenges. The purpose of this study was to analyze the challenges, capabilities and content of the curriculum in the era of society 5.0, and the process of curriculum development in the era 5.0. This writing uses a library search method with primary data sources articles, and journals related to the subject matter then analyzed and given an explanation. The challenge of the curriculum that is amid current technological developments is the lack of students mastering technology and the content of the curriculum itself, students are still unable to solve a problem they face. The challenges of this super-smart era must be passed and faced with the appropriate abilities to be able to solve problems easily. Of course, with the ability to think creatively, critically and successfully solve problems with confidence.